2010
DOI: 10.1016/j.jcrs.2009.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of endothelial cell loss after cataract surgery: Phacoemulsification versus manual small-incision cataract surgery

Abstract: There were no clinically or statistically significant differences in ECC loss or visual acuity between phacoemulsification and SICS, although there was a small difference in the astigmatic shift.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 19 publications
5
72
1
Order By: Relevance
“…by Gogate P et al in 2010. 11 were much higher (SICS-15.52%, phaco-15.33%) than values obtained in this study.…”
Section: Endothelial Cell Countcontrasting
confidence: 79%
See 1 more Smart Citation
“…by Gogate P et al in 2010. 11 were much higher (SICS-15.52%, phaco-15.33%) than values obtained in this study.…”
Section: Endothelial Cell Countcontrasting
confidence: 79%
“…11 However, the result by Ganekal S et al in 2014. 14 a statistically significant difference between the endothelial cell density was found at week 1 and 6 postoperatively between the SICS and the phaco group.…”
Section: Endothelial Cell Countmentioning
confidence: 98%
“…In this study, the mean ECD loss was approximately 80 cells/mm 2 (11.5%). Recent studies evaluating eyes with a normal preoperative ECD 7,20,28,29 report an endothelial cell loss of 1.8% to 15.0% after phacoemulsification. Previous studies 20,29 also found that the preoperative cell count was not predictive of corneal endothelial cell loss in eyes with a normal ECD.…”
Section: Discussionmentioning
confidence: 99%
“…One month after surgery, the corneal endothelial loss was 24.3% in the phacoemulsification group versus only 11.2% in the Aqualase group. Previous studies on endothelial cell changes following cataract surgery demonstrated very low or no significant cell count changes at all between 1 and 4 weeks, and even between 3 and 6 months [27,28,29]. …”
Section: Discussionmentioning
confidence: 99%